Rapid qualitative evidence syntheses (rQES) in health technology assessment: experiences, challenges, and lessons. (9th October 2020) - Majid, Umair; Weeks, Laura
Abstract: Healthcare decision makers are increasingly demanding that health technology assessment (HTA) is patient focused, and considers data about patients' perspectives on and experiences with health technologies in their everyday lives. Related data are typically generated through qualitative research, and in HTA the typical approach is to synthesize primary qualitative research through the conduct of qualitative evidence synthesis (QES). Abbreviated HTA timelines often do not allow for the full 6–12 months it may take to complete a QES, which has prompted the Canadian Agency for Drugs and Technologies in Health (CADTH) to explore the concept of "rapid qualitative evidence synthesis" (rQES). In this paper, we describe our experiences conducting three rQES at CADTH, and reflect on challenges faced, successes, and lessons learned. Given limited methodological guidance to guide this work, our aim is to provide insight for researchers who may contemplate rQES. We suggest several lessons, including strategies to iteratively develop research questions and search for eligible studies, use search of filters and limits, and use of a single reviewer experienced in qualitative research throughout the review process. We acknowledge that there is room for debate, though believe rQES is a laudable goal and that it is possible to produce a quality, relevant, and useful product, even under restricted timelines. That said, it is vital to recognize what is lost in the name of rapidity. We intend our paper to advance the necessary debate about when rQES may be appropriate, and not, and enable productive discussions around methodological development.